Residents' satisfaction with slum upgrading programme : case studies of C-KIPs in Jakarta , Indonesia - Usman , Mukhtar Kabir (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2013)
This research evaluates residents' perception of satisfaction with slum upgrading in Kampung Improvement Program (KIP) five (5) neighbourhoods, Jakarta, Indonesia. It identifies relevant macro and microscopic residential factors that contribute subjective well-being of Physical (water supply and sanitation), social (user status in society and behaviour), and economic (cost, willingness to pay, and management) variables which were analysed systematically. Based on person-environment congruity theory of residential satisfaction with physical and social environments, a mix quantitative and qualitative research method was applied in a cluster sample population of 400 residents. The research result suggests higher satisfaction with social than physical environment. Despite lack of regular supply of safe water and sanitation, residents are comfortable with their respective social settings. Social interaction and attachment are rated high by residents due to their linkage with demographic variables of household size, level of education and residents' length of stay in the environment. There is a significant difference in the satisfaction level between the five KIP neighbourhoods. The research findings qualitatively indicate that the variables of the home or house, environment, and management components of residential neighbourhood actually affected user satisfaction of the research sites. The findings further showed that while the home and environmental components of housing were satisfactory to the KIP dwellers, the management constituent seems to be below residents' expectations. Comparatively, qualitative data analysis indicate that both physical and social factors of a residential environment impact positively on personal and environmental quality of residents.In conclusion, residents' satisfaction with KIP neighbourhoods qualitatively correlates with their dwelling environment, access to portable water supply, environmental sanitation, and the social environment. In line with post positivist epistemology, there convergence of data sources on lack established relationship or difference between user satisfaction and physical attributes of KIP environment; and a strong correlation with social setting. These results are particularly timely for policymaking, literature and implementation of physical developmental action plans. This implies that settlement upgrading as an urban development strategy globally, though laudable, pose environmental challenges of satisfying the urban poor of the case study area.